Association between reproduction and immunity in the Egyptian mongoose Herpestes ichneumon is sex‐biased and unaffected by body condition. (10th November 2020) - Bandeira, V.; Virgós, E.; Azevedo, A.; Cunha, M.V.; Fonseca, C.
Abstract: The Egyptian mongoose ( Herpestes ichneumon ) is a carnivore in expansion on the western limits of Europe, where its reproductive ecology is unknown. In this study, we weighed and measured the gonads of 507 wild‐caught mongooses ranging its geographical distribution and all seasons of the year. Based on the variation in gonad weight, we determined periods of reproductive activity for females (December–June) and males (throughout the year), with both sexes showing a peak in gonad weight during February. We also identified periods of lactation (March‐August, n  = 10), gestation (December–July, n  = 20) and mean litter size (1–4 offspring, 2.75 ± 0.79, n  = 20). Next, we constructed two separate models to explain the variation in ovarian and testicular weight, using age cohort, season and region, spleen weight, body condition and the environmental variables habitat, river network and Egyptian mongoose density as predictors. Ovarian weight was influenced by season and spleen weight. Females with heavier ovaries were found in spring and simultaneously exhibited heavier spleens. Testicular weight was influenced by season, spleen weight and age, as well as several environmental variables. Males with lower spleen weight exhibited heavier testes, indicating a male‐specific negative association between reproductive and immune activity. Overall, the results of this study refine our knowledge on Egyptian mongoose reproductive ecology. They indicate that reproduction timing is determined by females, whose breeding is seasonal but who are unaffected by the set of environmental variables we tested, as opposed to males, who are influenced by these environmental conditions and seem to be reproductively active year round. These results also support a negative reproduction‐immunity trade‐off in males, that is independent of body condition and absent in females. Abstract : Herpestes ichneumon is a carnivore whose range is expanding on the western limits of Europe. It is negatively perceived by the hunting community, who believe it to predate mostly on small game species and to generate multiple and numerous litters. However, these concerns lacked scientific evidence. This study identified the species' reproductive, gestation and lactation periods, determined litter size and analyzed reproductive patterns. The results suggest that females are responsible for the timing of reproduction while males are active year‐round. Moreover, results suggest that the species demonstrates a sex‐biased association between reproduction and immunity that is unaffected by body condition, suggesting a reproduction‐immunity trade‐off in males. In females, where reproductive and immune organ mass are positively correlated, this trade‐off seems to be absent.